IMPLEMENTASI METODE SABAQ, SABQI, MANZIL DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL ALQUR’AN DI PONDOK PESANTREN MUTIARA ILMU KOTA JAMBI - suntari sukadi, suntari sukadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the implementation of the Sabaq, Sabqi, and Manzil methods in improving students’ Qur’anic memorization at Pondok Pesantren Mutiara Ilmu, Jambi City. The Sabaq, Sabqi, and Manzil methods are Qur’anic memorization approaches that emphasize the addition of new memorization, reinforcement of recent memorization, and continuous maintenance of previously memorized portions. This research employed a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation. The research informants consisted of tahfidz instructors and students of the tahfidz program at Pondok Pesantren Mutiara Ilmu, Jambi City. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the Sabaq, Sabqi, and Manzil methods at Pondok Pesantren Mutiara Ilmu, Jambi City has been carried out systematically, in a structured manner, and continuously. The Sabaq method is implemented daily as an effort to increase new memorization, the Sabqi method is applied to strengthen previously acquired memorization so that it is not easily forgotten, while the Manzil method is conducted as a weekly tasmi’ to maintain and stabilize earlier memorization. These three methods complement each other in maintaining a balance between the quantity and quality of students’ memorization. Memorization evaluation is carried out daily, weekly, and at the end of each semester to ensure fluency, accuracy of recitation, and consistency in memorization. Although several obstacles were found in the implementation of the methods, such as limitations in time management, students’ boredom, and differences in memorization abilities, overall the Sabaq, Sabqi, and Manzil methods proved to be effective in improving students’ Qur’anic memorization. This study concludes that the implementation of the Sabaq, Sabqi, and Manzil methods is able to produce students’ memorization that is more mutqin (strong and well-retained) and sustainable in the long term.